Ultrastructural and developmental features of the tessellated endoskeleton of elasmobranchs (sharks and rays). Issue 5 (24th August 2016) - Seidel, Ronald; Lyons, Kady; Blumer, Michael; Zaslansky, Paul; Fratzl, Peter; Weaver, James C.; Dean, Mason N.
Abstract: The endoskeleton of elasmobranchs (sharks and rays) is comprised largely of unmineralized cartilage, differing fundamentally from the bony skeletons of other vertebrates. Elasmobranch skeletons are further distinguished by a tessellated surface mineralization, a layer of minute, polygonal, mineralized tiles called tesserae. This 'tessellation' has defined the elasmobranch group for more than 400 million years, yet the limited data on development and ultrastructure of elasmobranch skeletons (e.g. how tesserae change in shape and mineral density with age) have restricted our abilities to develop hypotheses for tessellated cartilage growth. Using high‐resolution, two‐dimensional and three‐dimensional materials and structural characterization techniques, we investigate an ontogenetic series of tessellated cartilage from round stingray Urobatis halleri, allowing us to define a series of distinct phases for skeletal mineralization and previously unrecognized features of tesseral anatomy. We show that the distinct tiled morphology of elasmobranch calcified cartilage is established early in U. halleri development, with tesserae forming first in histotroph embryos as isolated, globular islets of mineralized tissue. By the sub‐adult stage, tesserae have increased in size and grown into contact with one another. The intertesseral contact results in the formation of more geometric (straight‐edged) tesseral shapes and the development of two important features of tesseral anatomy, which we describe here for the first time. The first, the intertesseral joint, where neighboring tesserae abut without appreciable overlapping or interlocking, is far more complex than previously realized, comprised of a convoluted bearing surface surrounded by areas of fibrous attachment. The second, tesseral spokes, are lamellated, high‐mineral density features radiating outward, like spokes on a wheel, from the center of each tessera to its joints with its neighbors, likely acting as structural reinforcements of the articulations between tesserae. As tesserae increase in size during ontogeny, spokes are lengthened via the addition of new lamellae, resulting in a visually striking mineralization pattern in the larger tesserae of older adult skeletons when viewed with scanning electron microscopy (SEM) in backscatter mode. Backscatter SEM also revealed that the cell lacunae in the center of larger tesserae are often filled with high mineral density material, suggesting that when intratesseral cells die, cell‐regulated inhibition of mineralization is interrupted. Many of the defining ultrastructural details we describe relate to local variation in tissue mineral density and support previously proposed accretive growth mechanisms for tesserae. High‐resolution micro‐computed tomography data indicate that some tesseral anatomical features we describe for U. halleri are common among species of all major elasmobranch groups despite large variation in tesseral shape and size. We discuss hypotheses about how these features develop, and compare them with other vertebrate skeletal tissue types and their growth mechanisms.